2010
DOI: 10.1029/2010gc003228
|View full text |Cite
|
Sign up to set email alerts
|

A multiscale approach to estimating topographically correlated propagation delays in radar interferograms

Abstract: [1] When targeting small amplitude surface deformation, using repeat orbit Interferometric Synthetic Aperture Radar (InSAR) observations can be plagued by propagation delays, some of which correlate with topographic variations. These topographically-correlated delays result from temporal variations in vertical stratification of the troposphere. An approximate model assuming a linear relationship between topography and interferometric phase has been used to correct observations with success in a few studies. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 134 publications
(123 citation statements)
references
References 36 publications
3
120
0
Order By: Relevance
“…They noted systematic differences between the two estimates of delay over the seaward and landward slopes of Mount Lebanon and suggested that the empirical method could not model stationary meteorological effects. A similar approach can also be applied at multiple scales, to identify and remove components of interferograms that correlate with topography across a variety of lengthscales [Shirzaei and Bürgmann, 2012;Lin et al, 2010]. However, all of these methods are susceptible to overcorrection of the data if elevation is correlated with the tectonic signal.…”
Section: Construction Of Interferograms and Atmospheric Contaminationmentioning
confidence: 99%
“…They noted systematic differences between the two estimates of delay over the seaward and landward slopes of Mount Lebanon and suggested that the empirical method could not model stationary meteorological effects. A similar approach can also be applied at multiple scales, to identify and remove components of interferograms that correlate with topography across a variety of lengthscales [Shirzaei and Bürgmann, 2012;Lin et al, 2010]. However, all of these methods are susceptible to overcorrection of the data if elevation is correlated with the tectonic signal.…”
Section: Construction Of Interferograms and Atmospheric Contaminationmentioning
confidence: 99%
“…Figure 4 shows the flow chart of the PLE method on the interferogram. The PLE method can account for lateral variations in space by estimating K m in multiple windows and can be applied in regions without removing a preliminary deformation [33]. The robust estimation technique is always available in each study area for a given day at a closet SAR acquisition.…”
Section: Power Law Model Based On Era-i Reanalysis (Ple)mentioning
confidence: 99%
“…Therefore, the selection of the band filter is not always trivial, as it requires empirical information about multi-scale dependent spectrums. However, we took advantage of the fact that the tropospheric signal is present at all wavelength scales to estimate the scaled factor from a spatial frequency band that was relatively insensitive to the other signals [33]. Similar to the original power law method [35,36], band filtering was applied to the phase and topography to select an appropriate band such that other phase contributions were negligible.…”
Section: Power Law Model Based On Era-i Reanalysis (Ple)mentioning
confidence: 99%
See 1 more Smart Citation
“…The success of this approach typically relies upon prior knowledge of either the location or spatial wavelength of deformation [62], of which we have neither in the Perth Basin. Predictive methods use external datasets, such as large-scale weather models [58,63] or GPS [64,65], to calculate and remove atmospheric artefacts.…”
Section: Reduction Of Error Sourcesmentioning
confidence: 99%